Mount Turu-Alty in the Mountain Altai and the Identification Problem of Ancient Shrines - A. I. Martynov; K. N. Sivina; R. D. Meshcherskiy (Вестник Кемеровского государственного университета, 2019)
The paper features the problem of identification of natural-historical shrines in the case of petroglyphs of Mount TuruAlty in Kosh-Agachsk district of the Altai Republic. Currently, all rock art sites in Southern Siberia are considered in scientific literature as rock art monuments. The authors studied the Mount Turu-Alty, the location of the petroglyphs, and other archaeological monuments in the neighborhood. As a result, they offer a different scientific interpretation of the monument as a natural-historical shrine. On the mountain top there is a rocky platform with a vertically standing large stone that faces the south and is completely covered with images. In the vicinity, there are several stone mounds. The mountain top is clearly visible from the foot on the sides of the southern slope. From this center, there are two ridges of large stones extending down to the right and left: they go round the terrace-like platforms of the steep southern slope. This natural formation has the shape of an amphitheater. On its top, there is an altar-like large stone. Standing at the foot of the southern slope, one cannot but feel the sacredness of this natural formation. On the large boulders that frame the southern slope, there are grouped and single etchings of animals. The field studies revealed images on 271 stones; 97 of the images are grouped, most are thematic. According to the plots, most of the images refer to the first millennium BC and the first half of first millennium AD. At the beginning of the first millennium BC, in the early Saka period, Mount Turu-Alty obviously acquired a special sacred status and began to function as a natural-historical shrine. The "altar" stone played a special role in this geological composition. It stands vertically on the top of the mountain, and its southern side is covered with 101 images of stylized deer, sheep, and goats. The stone is the main symbol of Turu-Alty. In the center, there are two large figures of deer flying to the east. All the other silhouettes are much smaller; all but one face the east. The animals are subject to eastward movement towards the sun. The authors consider the Turu-Alty complex as a natural-historical shrine from the period of the first millennium BC – first millennium AD.